Analisis tentang Pengembangan Instrumen Asesmen Five-Tier Berbasis Masalah Pada Pembelajaran IPA Fase B untuk Mengukur Kemampuan Berpikir Kritis dan Kreatif Peserta Didik Sekolah Dasar. - Iqbal Muhammad Syaifullah; Undang Rosidin; Fatkhur Rohman; Ryzal Perdana (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to develop an assessment instrument for problem-based Phase B science learning that is valid, practical and effective for measuring the critical and creative thinking abilities of students in elementary schools. This type of research is Research and Development (R&D), with development design referring to Borg & Gall theory. The population in this study was class IV students at SDN 4 Bumi Waras Bandar Lampung. Data collection tools use valid and reliable test instruments. The final average validation results from material experts, evaluation experts and language experts obtained a score of 87.75% with very valid criteria. The test results for the educator practitioners were 83% and the students were 82% with very practical criteria. The data analysis technique uses the One-Sample Z-Test to determine the correctness of the results of the assessment scores with a significance level of 95% (α 0.05), with a significance value of 0.023 obtained, indicating that the sig. value < 0.05 means H0 is rejected and H1 is accepted, so Effective assessment instrument for measuring students' critical and creative thinking abilities in elementary schools. Based on this research, it can be concluded that the assessment instruments for problem-based science learning are valid, practical and effective for measuring the critical and creative thinking abilities of students in elementary schools.